2017
DOI: 10.1108/jrit-09-2017-0022
|View full text |Cite
|
Sign up to set email alerts
|

On predicting academic performance with process mining in learning analytics

Abstract: Purpose The purpose of this paper is to propose a process mining approach to help in making early predictions to improve students’ learning experience in massive open online courses (MOOCs). It investigates the impact of various machine learning techniques in combination with process mining features to measure effectiveness of these techniques. Design/methodology/approach Student’s data (e.g. assessment grades, demographic information) and weekly interaction data based on event logs (e.g. video lecture inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 19 publications
(17 reference statements)
0
21
0
4
Order By: Relevance
“…Table 7 shows that machine learning methods outperformed logistic regression in all studies in terms of their classification accuracy in percent. To evaluate the performance of classifiers, the F1-score can also be used, which takes into account the number of positive instances correctly classified as positive, the number of negative instances incorrectly classified as positive, and the number of positive instances incorrectly classified as negative (Umer et al, 2017; for a brief overview of measures of diagnostic accuracy, see Šimundić, 2009). The F1-score ranges between 0 and 1 with its best value at 1 (perfect precision and recall).…”
Section: Profiling and Predictionmentioning
confidence: 99%
“…Table 7 shows that machine learning methods outperformed logistic regression in all studies in terms of their classification accuracy in percent. To evaluate the performance of classifiers, the F1-score can also be used, which takes into account the number of positive instances correctly classified as positive, the number of negative instances incorrectly classified as positive, and the number of positive instances incorrectly classified as negative (Umer et al, 2017; for a brief overview of measures of diagnostic accuracy, see Šimundić, 2009). The F1-score ranges between 0 and 1 with its best value at 1 (perfect precision and recall).…”
Section: Profiling and Predictionmentioning
confidence: 99%
“…Aluko, Daniel, Shamsideen Oshodi, Aigbavboa, & Abisuga, [3] compared the prediction accuracy of Support vector machine and logistic regression using a sample size of 102 architecture students for predicting the performance of students in academics and found that Support vector machine classifier is better than logistic regression in predicting students' academic performance. Umer, Susnjak, Mathrani, & Suriadi, [14] have used three Machine learning classification algorithms to predict the performance of students by recording their weekly performance in MOOCS environment. The Study revealed that combining process mining with the standard machine learning techniques improved the accuracy of the models.…”
Section: Review Of Literaturementioning
confidence: 99%
“…On a similar note, Mukala et al (2015) use process mining techniques to monitor and analyse student learning habits based on data collected from Massive Open Online Courses (MOOCs) establishing that successful students always watch videos in the recommended sequence, while the opposite is true for unsuccessful students. Related to MOOCs, Umer et al (2017) propose a process mining approach to enhance the student learning experience by combining different machine learning techniques with process mining features to measure the effectiveness of different techniques. The ultimate aim of that particular data-based approach is to help improve the student learning experience and reduce dropout rates in MOOCs.…”
Section: Higher Educationmentioning
confidence: 99%